Proses Pembuatan Biofuel dengan Metode perengakahan Menggunakan Katalis Padat - Agus Budianto; Ayuni Rita Sari; Yohana Winda Monica; Erlinda Ningsih; Esthi Kusdarini (Journal of Industrial Process and Chemical Engineering (JOICHE), 2021)
The development of population growth causes of fuels need increasing. Because ofthat reason, it necessary to create alternative fuels which are friendly to theenvironment to meet the fuels need in society. Fossil fuel is a non-renewable fuel.Biofuel as an alternative fuel can be taken as a solution to solve this problem. Thereviewd aim was to determine the effect of raw materials used on yield product andthe different effects of temperature and catalysts on the yield of special materials(gasoline, diesel, kerosene) biofuel. Biofuel production started from thepreparation of raw materials, catalylic, and catalytic cracking process using afixed bed reactor. Raw materials greatly affected yield product. The highest yieldproducts were being gotten from RBDPS raw materials of 93.29%. Biofuel fromused cooking oil and concentration of red sludge catalyst of 15% produced thehighest biofuel with gasoline compound of 73.86% and kerosene compound of26.14%. Biofuel from camelina oil with ZSM-5-Zn catalyst concentration of 30%produced the highest gasoline yield of 75.65%.